2013
DOI: 10.1097/mib.0b013e3182802b6e
|View full text |Cite
|
Sign up to set email alerts
|

A New Rapid Quantitative Test for Fecal Calprotectin Predicts Endoscopic Activity in Ulcerative Colitis

Abstract: FC determined by QPOCT was an accurate surrogate marker of "endoscopic remission" in UC and presented a good correlation with the FC-ELISA test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 29 publications
5
67
0
1
Order By: Relevance
“…This FC-QPOCT testing demonstrated a good correlation with the conventional enzymelinked immunosorbent assay test for FC determination 20,21 even for Crohn's disease and UC. 2,22 Because all patients had an active disease at the time of sample collection, the high-range FC-QPOCT kit was initially used for FC measurement in all samples. All samples scoring .1800 mg/kg were performed again after sample dilution to obtain their exact value.…”
Section: Fc Measurementmentioning
confidence: 99%
“…This FC-QPOCT testing demonstrated a good correlation with the conventional enzymelinked immunosorbent assay test for FC determination 20,21 even for Crohn's disease and UC. 2,22 Because all patients had an active disease at the time of sample collection, the high-range FC-QPOCT kit was initially used for FC measurement in all samples. All samples scoring .1800 mg/kg were performed again after sample dilution to obtain their exact value.…”
Section: Fc Measurementmentioning
confidence: 99%
“…In China, Jong's test was based on Nycotest Phical ELISA (Nycomed, Norway) kit (18). And in another study FC was measured by both Calpro Elisa and Buhlmann Elisa and it was concluded that Calpro Elisa is a more accurate method (19). Iglesias studies were done using Rapid test.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of FC-POCT (qualitative, semi-quantitative and quantitative) are available -and good correlations between the latter and ELISAs have been reported [54,[65][66][67][68]. However, it has yet to be established whether FC-POCT results call for ELISA confirmation, and the way in which quality should be monitored.…”
Section: Lactoferrin and Calprotectin: Biochemical Properties Pre-anmentioning
confidence: 99%
“…Calprotectin, a 36.5 kDa hetero-trimer, consisting of one S100A8 light chain and two S100A9 heavy chains belonging to the S100 calcium binding proteins family, is present in the cytoplasm of granulocytes and accounts for about 60% of soluble proteins; it is secreted extracellularly from stimulated neutrophils and monocytes or released by cell disruption or death [44]. Both lactoferrin and calprotectin have antimicrobial properties: histidine-based zinc-binding sequences (His-X-X-X-His motif) are involved in the antimicrobial activity of calprotectin, while the amino-terminal domain (lactoferricin) liberated by pepsin Røseth et al [47] CD and UC 77%/100% Solem et al [48] CD 54%/75% D'Incà et al [49] CD 77%/80% 81%/80% D'Incà et al [49] UC 75%/60% 78%/70% Sipponen et al [50] CD 77%/100% 87%/100% Schoepfer et al [51] UC 86%-93%/71%-88% Schoepfer et al [52] CD 89%/58% 68%/58% Sipponen et al [53] CD 80%/67% 80%/89% Lobatòn et al [54] UC 74%/90% 84%/38%…”
Section: Lactoferrin and Calprotectin: Biochemical Properties Pre-anmentioning
confidence: 99%
See 1 more Smart Citation